1994
DOI: 10.1016/s0741-5214(94)70221-7
|View full text |Cite
|
Sign up to set email alerts
|

Early inhibition of myointimal proliferation by angiopeptin after balloon catheter injury in the rabbit

Abstract: Coronary artery restenosis after percutaneous transluminal angioplasty occurs in more than 40% of patients. Angiopeptin, a stable synthetic octapeptide analogue of somatostatin, attenuates accelerated coronary artery myointimal thickening in rabbit cardiac allografts and myointimal thickening after arterial injury. In this study the temporal relationship between the angiopeptin treatment schedule and efficacy was explored. The relationship between inhibition of myointimal thickening by angiopeptin and inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Delaying treatment for as little as 8 h after injury abrogates the inhibitory effects of octreotide. This stresses the importance of early events immediately after vascular tissue injury, suggesting that octreotide inhibits the expression of early genes causally related to the response to vascular injury and thereby triggering vascular cell proliferation [11].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Delaying treatment for as little as 8 h after injury abrogates the inhibitory effects of octreotide. This stresses the importance of early events immediately after vascular tissue injury, suggesting that octreotide inhibits the expression of early genes causally related to the response to vascular injury and thereby triggering vascular cell proliferation [11].…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, it has also been demonstrated that analogues of octreotide inhibit myointimal proliferation after air drying injury in the rat and balloon injury in the rabbit. Octreotide analogues have also been shown to inhibit chronic coronary vascular disease in rabbit and rat cardiac transplant models [7,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiopeptin is a synthetic somatostatin analogue with antiproliferative effects on vascular smooth muscle cells, although its exact mechanism of action is unclear. 73,74 De Scheerder et al 75 studied the effects of angiopeptin loaded onto stents coated with polyorganophosphazene, a polymer known to induce an exaggerated inflammatory and proliferative response. At 6 weeks, a significant difference in the minimum luminal diameter and neointimal area between angiopeptin-treated arteries and untreated controls was noted in this model of accelerated restenosis in porcine coronary arteries.…”
Section: Stents Coated With Corticosteroids and Antimitotic Agentsmentioning
confidence: 99%